Research on key processing parameters of parallel seam welding of micro crystal resonator based on simulation experiment. (9th September 2020) - Hu, Jian; Xing, Saiding; Shan, Xiaorong; Yu, Xindong; Li, Gangyan
Abstract: Parallel Seam Welding (PSW) is the most widely used processing technology in micro crystal resonator packaging. PSW processing involves multiple parameters, and the design of processing plan in actual production lacks theoretical guidance, induces in high experiment cost and low accuracy of experimental results. In order to improve the design efficiency of PSW processing plan, the simulation experiment is designed for studying the effect of key processing parameters. The processing parameters involved in the simulation experiment were determined by analyzing the PSW processing. An electrical, thermal, and force coupled simulation model aiming at the physical process involved in PSW processing was established based on ANSYS. The single-factor experiment based on simulation model was designed in order to determine the effect and the experiment range of PSW processing parameters. In order to obtain the key processing parameters, the significance of PSW processing parameter to the packaging quality was calculated based on orthogonal experiment.